Serosurvey of Toxoplasma gondii and Leptospira spp. in Free-range Agoutis (Dasyprocta azarae) from an Urban Area of Southern Brazil - Yamakawa, Ana Carolina [UNESP]; Pellizzaro, Maysa [UNESP]; Joaquim, Samea Fernandes [UNESP]; Cunha, Graziela Ribeiro da; Weckerlin, Patricia; Martins, Camila Marinelli; Santos, Andrea Pires dos; Langoni, Helio [UNESP]; Lange, Rogerio Ribas; Biondo, Alexander Welker (Wildlife Disease Assoc, Inc, 2020)
Thirty-six free-ranging agoutis (Dasyprocta azarae) from an urban area of the municipality of Curitiba, a southern region of Brazil, were tested for antibodies against Toxoplasma gondii and Leptospira spp. Antibodies were present in 25% and 6% agoutis, respectively. No statistical differences were observed based on sex, age, and body mass of the agoutis. High T. gondii seropositivity indicated environmental contamination, whereas lower seropositivity of Leptospira spp. suggested low environmental contamination or low susceptibility.